Open design no cenário contemporâneo - Rodríguez Cabeza, Edison Uriel [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present work is a design look back about contemporary times and some changes caused by technologies and the new forms of collective actions in support of ideias that permit to acess, distribution of good, products and services for collectivity. The main aim of this research is explore and describe the contemporary context, especially in the Brazilian context. It was made an inquiry about Openness concept in different knowledge fields, aiming at a better and greather understanding of Openness. This work is dividing into three parts. The first part is the construction of Openness concept from different knowledge fields. The second part is a look about contemporary time, about new technologies and design. The third part is an analysis of Open Design and its practice in the Brazilian context. This research aims to contribute to better and more compressive understanding of contemporary design through one of its aspects: the Open Design. Also intends to contribute to dissemination and understanding of development products, systems and services generated by the free and commons-based-peer-production

O presente trabalho é um olhar do design sobre a contemporaneidade e em algumas de suas mudanças geradas pelas tecnologias e pelas novas formas de atuações coletivas em prol de ideias e ideias que permeiam o acesso, a distribuição e a produção de bens, produtos e serviços para a coletividade. O objetivo principal desta pesquisa é explorar e descrever o cenário contemporâneo do Open Design especialmente no contexto brasileiro. Foi elaborada uma indagação sobre o conceito de abertura (Openness) em diferentes campos do conhecimento visando maior e melhor entendimento da abertura. O trabalho está dividido em três partes, a primeira é a construção do conceito de abertura desde diferentes campos do conhecimento, a segunda parte é um olhar sobre a contemporaneidade, as novas tecnologias e o design, e a terceira é uma análise do Open Design e sua prática no contexto brasileiro. Esta pesquisa visa contribuir para um melhor e mais abrangente entendimento do design contemporâneo por meio de uma de suas vertentes, o Open Design. Pretende, ainda, colaborar para a disseminação e o entendimento do desenvolvimento de produtos, sistemas e serviços materiais e imateriais gerados pelo trabalho livre e colaborativo
Keywords: Desenho industrial; Tecnologia; Web 2.0; Civilização moderna; Cooperação; Industrial design